Penerapan Model Pembelajaran Berbasis Game Domatika (Domino Matematika) dalam Menumbuhkan Minat Belajar Matematika Siswa Fase C MIM Gembuk II - Nova Ayuningtyas; Suryatin; Afid Burhanuddin (PGSD STKIP PGRI Pacitan, 2026)
This study aimed to describe the implementation of the Domatika (Mathematics Domino) game-based learning model in fostering mathematics learning interest among Phase C students at MIM Gembuk II. This research employed a qualitative approach, with data collected through observations, interviews, and questionnaires. The research subjects consisted of two teachers and eight students involved in the mathematics learning process. The findings revealed that the implementation of the Domatika game was able to create a more active, interactive, and enjoyable learning environment. Based on the observation results, students appeared more enthusiastic, actively engaged in discussions, and more focused on solving mathematical problems through the game. The interview results indicated that both teachers and students responded positively to the use of the Mathematics Domino game, as it helped students understand mathematical concepts more easily. In addition, the questionnaire results showed an increase in students’ learning interest, which was reflected in their enjoyment, attention, and active participation during the learning process. Therefore, the implementation of the Domatika game-based learning model can serve as an effective alternative learning strategy for fostering students’ interest in learning mathematics.